(untitled) (Journal of Tikapur Multiple Campus, 2026)
Financial risk protection and efficient use of healthcare resources remain critical challenges for Nepal as a low-income country. This study examines beneficiaries’ perceptions of financial risk protection and service coverage under the National Health Insurance Scheme (NHIS) from a health economics perspective, with a focus on optimizing limited resources. The study aims to capture beneficiaries’ perception on satisfaction, challenges, and gaps in scheme implementation within the study area. Primary data were collected during the first quarter of 2025 from 62 NHIS-enrolled households across nine wards of Tikapur Municipality, Kailali district, using a structured questionnaire. Proportionate stratified sampling based on ward-level enrollment was applied, with purposive sampling within each stratum. The findings indicate that beneficiaries generally rate the NHIS positively in terms of financial security. However, notable weaknesses persist, particularly regarding emergency care support and the availability of health services. A major concern expressed by respondents is the exclusion of several essential medicines from the benefit package, especially those needed by vulnerable populations. In addition, the current annual coverage ceiling of NPR 100 thousands is widely perceived as insufficient to meet actual healthcare costs. These gaps highlight the need for operational and policy reforms. Expanding benefit packages and increasing coverage limits could enhance enrollee satisfaction, reduce out-of-pocket payments for healthcare, promote equity, and support Nepal’s progress toward universal health coverage.